If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = -2x + 16 Multiply g * x gx = -2x + 16 Reorder the terms: gx = 16 + -2x Solving gx = 16 + -2x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = 16x-1 + -2 Simplifying g = 16x-1 + -2 Reorder the terms: g = -2 + 16x-1
| 2(x+6)-5(x-7)=x-11 | | ax-b=cy | | ax-b=cyforx | | (3+z)(4z+9)=0 | | x+123=360 | | x+123=180 | | 0.6x+0.8=.28x+1.16 | | t=3m+3wform | | 20.5=x+11.5 | | 70=y+25.75 | | 0.09x+0.12(2x+43000)=39810 | | 6(n+10)-n=10 | | 20x^3-16x^2+15x-12=0 | | 0.09x+0.12(4x+48000)=91260 | | -10-4n=-15 | | (5x-2)-2(4x+1)=7x-2 | | (y+2)-y=2 | | 3x-2(2x-9)=4(2x-9)+8x | | 11-6y=38 | | 7=p+16 | | 19x-13=11x+35 | | 2077=31n | | 21x+13=9x+61 | | 0.88=121/x | | -3n+6n-5+7= | | 4x^3-15x^2-12x=0 | | 3w-7+6w-5= | | Ax+3=11 | | 2n^2-n+12=0 | | 3(p+5)=2(p-6)+p+27 | | 5(3x-11)-7x=11 | | 2n^2-n=-12 |